Methane yield and lag correlate with bacterial community shift following bioplastic anaerobic co-digestion. (September 2019) - Venkiteshwaran, Kaushik; Benn, Nicholas; Seyedi, Saba; Zitomer, Daniel
Abstract: Past plastic management practices have resulted in pollution. An improved management scenario may involve adding used bioplastic to anaerobic digesters to increase methane for renewable energy. In this work, effects of polyhydroxybutyrate (PHB) bioplastic anaerobic co-digestion with synthetic primary sludge on operation and microbial communities were investigated. Co-digesters treating sludge were co-fed 20% untreated or pretreated (55 °C, pH 12) PHB. Pretreament resulted in shorter lag (5 d shorter) before methane production increased after co-digestion. At steady-state, co-digesters converted 86% and 91% of untreated and pretreated PHB to methane, respectively. Bacterial communities were different before and after bioplastic co-digestion, whereas no archaeal community change was observed. Relative abundance of 30 significant bacteria correlated with methane production and lag following PHB addition. No previously known PHB degraders were detected following PHB co-digestion. Microbial communities in anaerobic digesters treating synthetic primary sludge are sufficiently capable of co-digesting PHB to produce additional methane. Highlights: Waste polyhydroxybutyrate (PHB) bioplastics can be co-fed to anaerobic digesters. PHB bioplastics were converted to methane with no change in digester function. Pretreatment of PHBs at high pH and temperature can reduce digester lag time. PHB co-digestion caused a shift in bacterial, but not archaeal communities. Thirty significant bacteria correlated with methane production and lag time.